Impact of Early Nasal Obstruction in Histological Development of and Physiological State - Guy Stéphane Padzys; Jean Marc Martrette; Marie Trabalon (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Introduction: Nasal obstruction is a risk factor in sleep-disordered breathing with a negative impact on the quality of life in humans Objective: In this study we determined whether histological development of olfactory bulb development could be influenced by an early temporary (3 d) nasal obstruction associated with physiological state. Methods: The rats were killed at specific time points after surgery. Plasma samples were taken for biochemical analyses, and histological measurements were performed. Shortly after nasal obstruction, the volumes of external plexiform (CPE), internal plexiform (CGI), and granule cell (CGr) was measured in both sexes of test rats compared with controls. Results and Conclusion: Reversible nasal obstruction was further associated with reduced dimensions of the volumes of CPE (male: 55%; female: 37%), CGI (male: 49%; female: 34%) and CGr (male: 70%; female: 47%). Basal corticosterone levels had increased in female rats, however, we observed the lower level of thyroid hormone, especially in male experimental group. We conclude that a 3-d nasal obstruction period in young rats leads to long-term hormonal changes was associated in modification of histological structural of olfactory bulb.